Understanding Immune Responses to Surgical Transplant Procedures in Stevens Johnsons Syndrome Patients - Soifer, Matias; Mousa, Hazem M.; Levy, Robert B.; Perez, Victor L. (Frontiers in Medicine, 2021)
Stevens Johnsons syndrome (SJS) is a mucocutaneous disorder caused by an autoimmune response most commonly to medications. Unless it is properly managed in the acute setting, this entity can affect the ocular surface causing chronic cicatrizing conjunctivitis with limbal stem cell deficiency and lid anomalies which ultimately result in corneal opacities that may limit patients’ visual acuity. When this stage is reached, some patients might need to undergo some form of corneal and/or limbal stem cell transplantation that exposes an already sensitized immune system to a new alloantigen. While the innate immunity plays a role in corneal graft survival, adaptive immune responses play a major part in corneal graft rejection and failure, namely through CD 4+ T cell lymphocytes. Hence, the management of the immune response to surgical transplant procedures in SJS patients, involves a dual approach that modulates the inflammatory response to a new alloantigen in the context of an autoimmune sensitized patient. This review will explore and discuss current perspectives and future directions in the field of ocular immunology on how to manage SJS immune response to ocular surgical procedures, reviewing systemic and local immunosuppressive therapies and protocols to adequately manage this debilitating condition.